Prerequisites for the Diagnosis - Süha Bozbay; Oktay Demirkıran (Türk Yoğun Bakim Derneği Dergisi, 2023)

(untitled)
Brain death is death according to neurological criteria and is defined as the complete and permanent loss of all functions of the brain, including those of the brain stem, expressed as an unresponsive coma with loss of brain stem reflexes. Making this diagnosis both prevents the intensive care beds from being occupied in vain and is important in terms of being a donor in organ transplantation. Although there are differences between countries in the diagnosis of brain death, the prerequisites for the diagnosis should be carefully evaluated.